Social validation sebagai mediator pengaruh price pada impulsive purchase - Maulana, Adit Anugrah; Fikriah, Nur Laili (Journal of Management and Digital Business, 2026)
This study aims to analyze the effect of price on impulsive purchasing with social validation as a mediating variable among consumers of Adidas running shoes in Malang City. The increasing trend of running and the dominance of the Adidas brand in the sports shoe market make consumer impulsive purchasing behavior an important phenomenon to study. This study uses a quantitative approach with a survey method by distributing questionnaires to 120 respondents selected using purposive sampling. Data analysis was performed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of SmartPLS 3 software. The results show that price has a significant effect on impulsive purchase and social validation. In addition, social validation was also found to have a significant effect on impulsive purchases. Other findings indicate that social validation significantly mediates the effect of price on impulsive purchase. The results of this study indicate that price is not only perceived as economic value, but also as a social signal that can encourage impulsive purchasing behavior among consumers in the context of sports products.